A Discourse Analysis of TEDx Talks Video Entitled “Break The Ceiling Glass” By Prilly Latuconsina - Denti Zentia Putri; Safnil Arsyad (Journal of English for Specific Purposes in Indonesia, 2023)
Women have always been associated with societal standards. The current societal standards are considered by society not to make quality women because they are only fixated on the assumption that women are creatures who always depend on other people. Like a new article entity that leads "Break the glass ceiling". In this case, a young girl is urged to follow society's assumption that women who are old enough get married immediately and don't need to continue their education and explore the outside world to add value to themselves. The article illustrates that today's adolescents are concerned about the statement of marrying young, then thinking that after marriage their life will be better without adequate knowledge for both material and emotional fulfillment d. This research is qualitative research with a review of Foucault's critical discourse analysis method, from the perspective of discourse analysis critical from Alba-Juez (2009). The results of this media discourse want women not to follow the mindset of the ancient society which made women not independent emotionally and materially.